2009
DOI: 10.1152/ajprenal.90610.2008
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17 upregulation in human renal disease: a role in modulating TGF-α availability?

Abstract: A disintegrin and metalloproteinase (ADAM)17 sheds growth factors from the cell membrane, including epidermal growth factor receptor (EGFR) ligand transforming growth factor (TGF)-alpha. In mice, angiotensin II infusion induces renal fibrosis via ADAM17-mediated TGF-alpha shedding and subsequent EGFR activation. Pharmacological ADAM17 inhibition reduced renal fibrotic lesions and improved renal function, positioning ADAM17 as a promising target of intervention in renal disease. We studied ADAM17 expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 37 publications
3
84
0
1
Order By: Relevance
“…Initial reports indicate ADAM17 and cleavage of its substrates may be involved in kidney disease and can also contribute to the progression of diabetes (1,3,9,10,15,20,21,26,29,33,35,40,42,45,47). We hypothesized that ADAM17 plays a key role in ECM accumulation in DN.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Initial reports indicate ADAM17 and cleavage of its substrates may be involved in kidney disease and can also contribute to the progression of diabetes (1,3,9,10,15,20,21,26,29,33,35,40,42,45,47). We hypothesized that ADAM17 plays a key role in ECM accumulation in DN.…”
Section: Resultsmentioning
confidence: 98%
“…ADAM17, a member of this ADAM family of MMPs, was originally described as the sheddase of tumor necrosis factor-␣, referred to as TNF␣-converting enzyme (4, 34). In addition, ADAM17 is also responsible for cleaving membrane-bound growth factors and receptors such as transforming growth factor-␣ (TGF␣), heparin-bound epidermal growth factor (HB-EGF), TNF receptor I and II, adhesion molecules, proinflammatory molecules, amyloid precursor protein, and ErbB4 (4,12,17,28,34,39,41).There is evidence that ADAM17 plays a role in the pathogenesis of DN (1,3,10,11,20,21,26,29,33,35,40,42,47,48). Studies in mesangial cells showed that glucose activates ADAM17 and EGF receptor (EGFR) and regulates profibrotic TGF␤ and the accumulation of matrix proteins (48,(51)(52)(53).…”
mentioning
confidence: 99%
“…50 ADAM plays an important role in modulation of cell signaling in physiology and pathophysiology. [50][51][52] Studies on cultured cell and kidney slices indicated that a-secretase (ADAM 10/ 17) and b-secretase modulate aKlotho ectodomain shedding and becoming soluble aKlotho protein, 18,19 by acting on two cleavage sites: one close to the juxtamembrane region (aa 950 approximately981) and another between the KL1 and KL2 domains. 53 To examine if secretases modulate circulating aKlotho in vivo, we injected a-secretase inhibitor doxycline hyclate and/or b-secretase inhibitor III into the intraperitoneal cavity of normal mice for 2 days and determined serum aKlotho in 48 hours.…”
Section: Resultsmentioning
confidence: 99%
“…These ADAM17-specific staining patterns were in line with a study by Melenhorst et al, who analyzed ADAM17 mRNA distribution in renal diseases. 48 The staining patterns of biopsies from patients with active AAV draw a completely different picture. So far, we could only speculate about the nature of these changes.…”
Section: Discussionmentioning
confidence: 99%